EVALUASI AUDIT MANAJEMEN SUMBER DAYA MANUSIA TERHADAP PENINGKATAN KINERJA KARYAWAN PADA PT. CITRA BUMI SUMATERA PALEMBANG - Andini Utari Putri (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
This study aims for this study to determine how the implementation of human resource management audits in improving employee performance at PT Citra Bumi Sumatera Palembang. This study uses primary data and secondary data by collecting data from observations, documentation and interviews. The analysis technique used in this research is descriptive qualitative by analyzing the data conducted by the author, the next step is compiling a list of findings in 2012, 2013, and 2014 in connection with the implementation of human resource management audits which will then be given recommendations for these findings. so that it is expected that it will be used as corrective action and material for improvement. The results of the research conducted showed that the Human Resources Audit conducted by PT. Citra Bumi Sumatera Palembang is relatively good enough and the factors of implementing the orientation and placement functions as well as the factors of implementing the training and development functions have not played a role in improving employee performance.